INFINITE DISK AREA CALCULATION EQUATION AND KISAA CONSTANT - Ali Hameed Yassir (University of Thi-Qar Journal, 2019)
There are many difficulties and high complexity today of using traditional equations to calculate the area or circumference of any circular shape, because it cannot be only done by knowing only specific part of circle (disk) curve length (arc) or its diameter (some parameters), Many equations might be apply to compute the circular shapes (area, circumference), but these equations are so limited because these equations work through specific, limited domain, its variables (parameters) must be detected, well known and sometimes cannot be existed. It is a great thing to find new equation to compute any unknown circular area (disk) by using only one knowing (dynamic constant or one parameter). Kisaa constant (the knowing value) that I discovered, represents the hole domain that can any circle (disk) area occupies it in all available space, Using of this equation in the computation of circle diameter is in two cases: First, Circle (disk) that its radius begins from one centimeter and increases to infinite, Second, Circle (disk) that its radius begins from less than one centimeter and decreases to infinite. This new equation by its parameter Kissa constant enables anyone to compute directly, accurately and quickly any unknown circle (disk) area in different scientifically or researching fields like mathematics, physics, medicine or astronomy. Author suggests these two new equations to assist an industrial technologies and to increase the precision in the calculations through building and programming devices to calculate area and other belongings. These equations also help scientists in all fields such as space science to calculate the diameters of celestial bodies and give more accruing predictions of the vacuum and expansion of the universe.